2017
DOI: 10.1787/9789264286207-en
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Characterisation from a Waste and Materials End-State Perspective

Abstract: is a unique forum where the governments of 35 democracies work together to address the economic, social and environmental challenges of globalisation. The OECD is also at the forefront of efforts to understand and to help governments respond to new developments and concerns, such as corporate governance, the information economy and the challenges of an ageing population. The Organisation provides a setting where governments can compare policy experiences, seek answers to common problems, identify good practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Effective characterization allows the extent and nature of contamination to be determined, providing crucial evidence to support facility dismantling, the management of material and waste, protection of workers, the public and the environment, and associated cost estimations. [9] In March 2011, the nuclear reactors of the Fukushima Daiichi Nuclear Power Plant (FDNPP) of the Tokyo Electric Power Company were damaged by the Great East Japan Earthquake and subsequent tsunami. Several reports have revealed that nuclear fuel materials such as uranium, plutonium, and curium were released into the environment in trace amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Effective characterization allows the extent and nature of contamination to be determined, providing crucial evidence to support facility dismantling, the management of material and waste, protection of workers, the public and the environment, and associated cost estimations. [9] In March 2011, the nuclear reactors of the Fukushima Daiichi Nuclear Power Plant (FDNPP) of the Tokyo Electric Power Company were damaged by the Great East Japan Earthquake and subsequent tsunami. Several reports have revealed that nuclear fuel materials such as uranium, plutonium, and curium were released into the environment in trace amounts.…”
Section: Introductionmentioning
confidence: 99%